Fracture Morphology Analysis of Frozen Red Sandstone under Impact - Yang Yang; Niannian Zhang; Jianguo Wang (Shock and Vibration)
The deformation and failure characteristics of red sandstone under subzero temperature were studied by the split Hopkinson pressure bar (SHPB) dynamic impact test. The effects of different subzero temperatures on rock strength properties, fractal dimension, and dissipated energy were analyzed combined with microfracture morphology. The reasons for rock dynamic mechanical property deterioration under lower subzero temperatures were revealed. The research shows that low subzero temperature will cause “frostbite” of red sandstone. Under high strain rate loading, the rock will quickly lose its bearing capacity, and its dynamic mechanical strength will drop sharply. The dissipated energy WL of the frozen rock specimen is positively correlated with the fractal dimension D and closely related to the macroscopic failure characteristics. It could be concluded that greater dissipation energy leads to more serious damage of rock and accordingly results in a larger fractal dimension. Fracture morphology analysis shows that the lower subzero temperature generated remarkable cracks in the material interface of the red sandstone. The damage of the red sandstone could be explained by the fact that the crack tip had low plastic deformation ability under high strain rate loading and the composition of cement was vulnerable to the subzero temperature effect.